2014
DOI: 10.4028/www.scientific.net/amm.592-594.883
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Machining Parameters in CNC Turning of EN3 Low Carbon Steel Using Genetic Algorithm and Response Surface Methodology

Abstract: Burrs are bottleneck of precision machining and automation production. Burrs are formed in every edges and faces, during the turning process, which affects the quality level of surface roughness. In this paper the experimental study of EN3 low carbon steel were carried out to minimize the surface roughness using response surface methodology and genetic algorithm. Tungsten Carbide was used as a cutting tool for this turning operation. Machined samples are examined under Scanning Electron Microscope (SEM) for bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Feed is the major influencing parameter in turning steel. Ravi Kumar et al [9] experimented turning process on low carbon steel EN3 and found the spindle speed, feed and depth of cut as impelling parameters. The optimal input parameters were found by applying genetic algorithm (GA) and response surface methodology (RSM).…”
Section: Introductionmentioning
confidence: 99%
“…Feed is the major influencing parameter in turning steel. Ravi Kumar et al [9] experimented turning process on low carbon steel EN3 and found the spindle speed, feed and depth of cut as impelling parameters. The optimal input parameters were found by applying genetic algorithm (GA) and response surface methodology (RSM).…”
Section: Introductionmentioning
confidence: 99%